Antecedents and Consequences of Individual Performance: Analysis of Turnover Intention Model (Empirical Study of Public Accountants in Indonesia) - Raza, Hendra; ., Erlina; ., Prihatin Lumban Raja (Journal of Economics and Behavioral Studies, 2014)
This study aims to examine empirically the antecedents of individual performance on its consequences of turnover intention in public accounting firms. There are eight variables measured which consists of auditors’ empowerment, innovation, professionalism, role ambiguity, role conflict, organizational commitment, individual performance and turnover intention. Data analysis is based on 163 public accountant using the Structural Equation Modeling assisted with an application of the Analysis Moment Structure (AMOS). The findings have revealed that the model is acceptable and successfully proves on a significant influence of the auditors’ innovation on the role ambiguity, professionalism on the role ambiguity, empowerment on the role conflict, innovation on the role conflict, professionalism on the role conflict, role conflict on the organizational commitment, role ambiguity on the auditors’ performance, organizational commitment on the auditors’ performance, auditors’ empowerment on the turnover intention, innovation on the turnover intention, professionalism on the turnover intention, organizational committment on the turnover intention, auditors’ performance on turnover intention. The new variables of auditors’ empowerment and innovation in the model as well as the direct influence of performance on turnover intention are successfully proven.